2022
DOI: 10.1016/j.vaccine.2022.01.007
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant SARS-CoV-2 receptor-binding domain expressed in an engineered fungal strain of Thermothelomyces heterothallica induces a functional immune response in mice

Abstract: Since the beginning of the COVID-19 pandemic, the development of effective vaccines against this pathogen has been a priority for the scientific community. Several strategies have been developed including vaccines based on recombinant viral protein fragments. The receptor-binding domain (RBD) in the S1 subunit of S protein has been considered one of the main targets of neutralizing antibodies. In this study we assess the potential of a vaccine formulation based on the recombinant RBD domain of SARS-CoV-2 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Likewise, a previous study reported high immunogenicity of the RBD 70 and another one could show that strong spike‐ and especially RBD‐specific circulating T follicular helper cells correlate with the maintenance of humoral immunity 71 . In addition to the already known protective aspect of neutralising anti‐RBD antibodies, 20 these findings support the upcoming efforts to develop a vaccine based on the SARS‐CoV‐2 spike RBD 72–74 . Such a vaccine could likely induce protective, spike‐specific CD4 + T‐cell responses in a substantial proportion of patients.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Likewise, a previous study reported high immunogenicity of the RBD 70 and another one could show that strong spike‐ and especially RBD‐specific circulating T follicular helper cells correlate with the maintenance of humoral immunity 71 . In addition to the already known protective aspect of neutralising anti‐RBD antibodies, 20 these findings support the upcoming efforts to develop a vaccine based on the SARS‐CoV‐2 spike RBD 72–74 . Such a vaccine could likely induce protective, spike‐specific CD4 + T‐cell responses in a substantial proportion of patients.…”
Section: Discussionsupporting
confidence: 66%
“… 71 In addition to the already known protective aspect of neutralising anti‐RBD antibodies, 20 these findings support the upcoming efforts to develop a vaccine based on the SARS‐CoV‐2 spike RBD. 72 , 73 , 74 Such a vaccine could likely induce protective, spike‐specific CD4 + T‐cell responses in a substantial proportion of patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some animals exhibited CMI response in spleen against RBD. Taking together, we consider that the combination of N+ODN-39M constitutes a promising nasal vaccine component that can be added to the list of enhancers of RBD immune response by this route (Cao et al, 2021), (Du et al, 2021), (Jearanaiwitayakul et al, 2021), (Lazo et al, 2022), (Schild, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the C1-produced RBD-C-tag recombinant subunit antigen specifically and strongly binds hACE2 receptors and, thus possesses RBD-specific antigen epitope conformation(s) functional for hACE2 receptor binding, and therefore, has been also utilized for the production of the SARS-CoV-2 S protein RBD as a potential vaccine candidate. 15 …”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the C1-produced RBD-C-tag recombinant subunit antigen specifically and strongly binds hACE2 receptors and, thus possesses RBD-specific antigen epitope conformation(s) functional for hACE2 receptor binding, and therefore, has been also utilized for the production of the SARS-CoV-2 S protein RBD as a potential vaccine candidate. 15 One of the most important steps in vaccine development is preclinical safety assessment in animals. This aims to predict the safety of the vaccine's clinical use in humans, to decrease the chance for adverse effects in clinical trial participants, and to provide information for vaccination protocols.…”
Section: Introductionmentioning
confidence: 99%